2019
DOI: 10.31235/osf.io/vs8w3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The airification of cities. Making sense of the impact of peer to peer short term letting on urban functions and economy

Abstract: An in-depth look into the mechanics of short term rentals in Italy. The study is based on a vast dataset comprising of all the properties listed on the Airbnb website in 10 major cities in the years 2015, 2016 and 2017. We discuss the spatial patterns of Airbnb supply and demand within and between cities, we then hypothesize on the possible drivers of the Airbnb offer and suggest a possible way to assess whether Airbnb supply could be driven by an economic advantage of short-term over long term letting. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 8 publications
1
30
0
3
Order By: Relevance
“…Evidence about the spatial effects of accommodation platforms is indeed ambivalent (for a review, see Guttentag, 2019). Short-term rentals, it has been shown, are causing both the overtouristification of already highly touristified city centres (Alizadeh et al, 2018;Arias Sans & Quaglieri Dom ınguez, 2016;Ben ıtez-Aurioles, 2018;Picascia et al, 2017) and the invasion and gentrification of non-touristic neighbourhoods (Cocola-Gant, 2016;Ioannides et al, 2019;Wachsmuth & Weisler, 2018). This apparent ambivalence can easily be solved by assuming that short-term rentals are much more diffused and widespread all over the cities' central and nearcentral areas than hotels and traditional accommodation facilities (Celata, 2017;Guti errez et al, 2017;Gy odi, 2017).…”
Section: The How and Where Of Platform-mediated Overtourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence about the spatial effects of accommodation platforms is indeed ambivalent (for a review, see Guttentag, 2019). Short-term rentals, it has been shown, are causing both the overtouristification of already highly touristified city centres (Alizadeh et al, 2018;Arias Sans & Quaglieri Dom ınguez, 2016;Ben ıtez-Aurioles, 2018;Picascia et al, 2017) and the invasion and gentrification of non-touristic neighbourhoods (Cocola-Gant, 2016;Ioannides et al, 2019;Wachsmuth & Weisler, 2018). This apparent ambivalence can easily be solved by assuming that short-term rentals are much more diffused and widespread all over the cities' central and nearcentral areas than hotels and traditional accommodation facilities (Celata, 2017;Guti errez et al, 2017;Gy odi, 2017).…”
Section: The How and Where Of Platform-mediated Overtourismmentioning
confidence: 99%
“…The case study cities have been identified based on the number of short-term rentals listed on the accommodation platform Airbnb.com (Picascia et al, 2017). All of these cities have seen a proliferation of initiatives and social movements denouncing the effects of overtourism and short-term rentals, in particular in terms of housing availability for residents or students.…”
Section: Introductionmentioning
confidence: 99%
“…One example of this type of unregulated activities is provided by the fast growth in Rome of networked hospitality businesses. For example, in 2015 the Airbnb network gained 7.1% of all the houses in Rome's city center, and this number rose to 8% in 2016 (Picascia et al 2017). It is an impressive amount if we consider the small surface of Rome's historical area.…”
Section: The Second Stage the Retreat Of The Publicmentioning
confidence: 99%
“…In addition to the fact that Airbnb is related to the saturation of the carrying capacity of many cities, it has also been responsible for substantially changing the morphology of the destinations where it is present [49]. Likewise, these types of rentals are responsible for the overtourism of urban centers that were already very touristy [14,50,51] and the invasion and gentrification of neighborhoods [21,[52][53][54].…”
Section: Negative Effects Of Tourism Authorsmentioning
confidence: 99%